THE SEMANTICS OF ACCOUNTING. - Pinger, R. W. (The Accounting Review, 1954)
The article focuses on the semantics of accounting. In teaching engineering economy to technical students the objective is not to make economists, entrepreneurs or accountants out of them. It is simply to impart some knowledge of the concepts and terminology employed by these professions, particularly those ordinarily encountered in engineering enterprises. Of the three fields, accounting is probably as important as any, but the student is often annoyed to find its language quite unstandardized, by comparison with that of engineering and science. It is not likely that the accounting profession will standardize its terminology merely to please the scientific and engineering world, in or out of college. Even if it were willing to do so, management, silently respectful in the presence of technical etymology, might have definite and reactionary opinions on any matter of commercial nomenclature. Common stocks, however, must now be sold to everyone with forty dollars more than his monthly needs.